Normal faulting along the western side of the Matese Mountains: Implications for active tectonics in the Central Apennines (Italy). (January 2016) - Boncio, Paolo; Dichiarante, Anna Maria; Auciello, Eugenio; Saroli, Michele; Stoppa, Francesco
Abstract: We provide new field data from geologic mapping and bedrock structural geology along the western side of the Matese Mts in central Italy, a region of high seismicity, strain rates among the highest of the entire Apennines (4–5 mm/yr GPS-determined extension), and poorly constrained active faults. The existing knowledge on the Aquae Iuliae normal fault (AIF) was implemented with geometric and kinematic data that better constrain its total length (16.5 km), the minimum long-term throw rate (0.3–0.4 mm/yr, post-late glacial maximum, LGM), and the segmentation. For the first time, we provide evidence of post-350 ka and possibly late Quaternary activity of the Ailano – Piedimonte Matese normal fault (APMF). The APMF is 18 km long. It is composed of a main 11 km-long segment striking NW–SE and progressively bending to the E–W in its southern part, and a 7 km-long segment striking E–W to ENE-WSW with very poor evidence of recent activity. The available data suggest a possible post-LGM throw rate of the main segment of ≳0.15 mm/yr. There is no evidence of active linkage in the step-over zone between the AIF and APMF (Prata Sannita step-over). An original tectonic model is proposed by comparing structural and geodetic data. The AIF and APMF belong to two major, nearly parallel fault systems. One system runs at the core of the Matese Mts and is formed by the AIF and the faults of the Gallo-Letino-Matese Lake system. The other system runs along the western side of the Matese Mts and is formed by the APMF, linked to the SE with the Piedimonte Matese – Gioia Sannitica fault. The finite extension of the APMF might be transferred to the NW towards the San Pietro Infine fault. The nearly 2–3 mm/yr GPS-determined extension rate is probably partitioned between the two systems, with a ratio that is difficult to establish due to poor GPS coverage. The proposed model, though incomplete (several faults/transfer zones need further investigations), aids in the seismotectonic interpretation of poorly-known earthquakes (e.g., 346/355 AD earthquake on the Ailano – Piedimonte Matese – Gioia Sannitica fault system), and stimulates and further orients seismotectonic investigations aimed at constraining the segmentation pattern and seismogenic potential of the area. Highlights: New field data for the high-seismicity, high-strain rate Matese area in central Italy. First evidence of post-350 ka activity for Ailano – Piedimonte Matese normal fault. New constraints for Aquae Iuliae normal fault and Prata Sannita step-over zone. Segmentation of active normal faults and partitioning of active strain rate in Matese. Seismotectonic interpretation of poorly-known earthquakes (e.g., 346/355 AD).